Association between attention deficit hyperactivity disorder and bruxism: A systematic review protocol - Anna Carolina Pereira Thimoteo; Júlia Meller Dias de Oliveira; Helena Polmann; Patrícia Pauletto; Cristine Miron Stefani; Graziela De Luca Canto; Lauren Bohner (PLoS ONE, 2025)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder characterized by the primary symptoms of inattention, disorganization, and/or hyperactivity-impulsivity. Bruxism is a repetitive activity of the chewing muscles characterized by clenching and grinding of the teeth and forceful mandibular movements. Various physiological and psychosocial factors, including attention deficit, depression, stress, and anxiety, have been associated with bruxism. The aim of this systematic review protocol is facilitating the understanding of the systematic review methods and promote transparency in the research. The systematic review will investigate whether there is evidence regarding the association between ADHD and bruxism. The search will be conducted on six databases. Gray literature will be explored through Google Scholar and ProQuest Dissertations & Theses Global. Lists of references of included studies and experts in the field will be consulted. Observational studies that present data comparing a group of individuals with ADHD and a group of individuals without ADHD as well as an analysis of the presence of bruxism will be included. Included studies can detect bruxism based only on a positive self-report (or parental report), clinical inspection, or instrumental assessment. The selection of studies will occur in two phases by two authors. The risk of bias in the included studies will be assessed using JBI tools. A narrative synthesis will be performed. If feasible, a quantitative synthesis will be carried out through pairwise meta-analysis. Odds ratios with 95% confidence intervals will be calculated using the random effects model. This protocol is characterized by its rigorous methodology, which involves an exhaustive search across six databases, as well as gray literature sources, reference lists, and expert consultation, thereby augmenting the comprehensiveness and reliability of the findings. This protocol was registered in PROSPERO under the number CRD42024538099.